Exploring community perceptions of crime and crime prevention through environmental design (CPTED) in Botswana. - Cozens, Paul; Melenhorst, P. (British Society of Criminology, 2014)
Crime Prevention through Environmental Design (CPTED) is a place-based crime strategy located firmly within the perspectives of post-industrial Western societies. It has been implemented in many developed countries in the United Kingdom (UK), North America, Europe, Australia, New Zealand and in parts of Asia and the Middle East. However, CPTED has found limited formalised use in the developing world. This paper investigates the application of CPTED to a non-Western setting in the developing world. It explores to what extent local perceptions of community safety align with the Western principles of CPTED in a case study of Gaborone, Botswana. The findings suggest the Western CPTED Audit and the non-Western Setswana respondents in the Community Safety Survey both indicated there were low levels of CPTED features in the environment. However, the local respondents reported high levels of personal safety.The features of CPTED appear to be identified in similar ways but may not be linked to feelings of personal safety in a non- Western context in the same way. CPTED concepts appear to be intact - but their transferability as a crime prevention strategy remains in question.